Impairment measures versus inflammatory RODS in GBS and CIDP: a responsiveness comparison. Issue 3 (September 2015) - Vanhoutte, Els K.; Draak, Thomas H. P.; Gorson, Kenneth C.; van Nes, Sonja I.; Hoeijmakers, Janneke G. J.; Van der Pol, W.‐Ludo; Notermans, Nicolette. C.; Lewis, Richard A.; Nobile‐Orazio, Eduardo; Léger, Jean‐Marc; Van den Bergh, Peter Y. K.; Lauria, Giuseppe; et al.
Abstract This study aimed to 'define responder' through the concept of minimum clinically important differences using the individually obtained standard errors (MCID‐SE) and a heuristic 'external criterion' responsiveness method in patients with Guillain‐Barré syndrome (GBS) and chronic inflammatory demyelinating polyradiculoneuropathy (CIDP). One hundred and fourteen newly diagnosed or relapsing patients (GBS: 55, CIDP: 59) were serially examined (1‐year follow‐up). The inflammatory Rasch‐built overall disability scale (I‐RODS), Rasch‐transformed MRC sum score (RT‐MRC), and Rasch‐transformed modified‐INCAT‐sensory scale (RT‐mISS) were assessed. Being‐a‐responder was defined as having a MCID‐SE cut‐off ≥1.96. Also, the correlations between patients' scores on each scale and the EuroQoL health‐status 'thermometer' (external criterion) were determined (higher correlation indicated better responsiveness). In both diseases, the SEs showed a characteristic 'U'‐shaped dynamic pattern across each scales' continuum. The number of patients showing a meaningful change were higher for the I‐RODS > RT‐MRC > RT‐mISS and were in GBS higher than CIDP patients. The MCID‐SE concept using Rasch‐transformed data demonstrated an individual pattern of 'being‐a‐responder' in patients with immune‐mediated neuropathies, and the findings were validated by the external criterion responsiveness method. The I‐RODS showed greater responsiveness compared with the MRC and INCAT‐sensory scales, and its use is therefore recommended in future trials in GBS and CIDP.